The Relationship Between Fat Intake and Pocket Money with The Incidence of Overweight in Teenagers at SMA Negeri 1 Toroh - Fitriyani, Ulfia; Setiyaningrum, Zulia (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Overweight is a prevalent nutritional issue among adolescents and increases the risk of future health problems such as cardiovascular disease and diabetes mellitus. Key contributing factors include high fat intake and the amount of pocket money, which can influence dietary habits. Objective: This study aimed to analyze the relationship between fat intake and pocket money with the incidence of overweight in adolescents at SMA Negeri 1 Toroh. Method: A cross-sectional design was used with a sample of 90 students was selected using proportionate stratified random sampling. Data collection involved a 3x24-hour food recall to assess fat intake, a questionnaire on pocket money, and anthropometric measurements to determine overweight status. The Pearson product moment test was used to analyze the relationship between fat intake and overweight, while the Spearman rank test assessed the relationship between pocket money and overweight. Results: Most respondents had a deficient fat intake (41.1%), medium-level pocket money (38.9%), and a 41.1% prevalence of overweight. Statistical analysis revealed a significant relationship between fat intake and overweight (p = 0.001) and between pocket money and overweight (p = 0.017). Conclusion: Both fat intake and pocket money are significantly associated with the incidence of overweight among adolescents.